Seawater corrosion resistant cable and preparation method thereof
By using a combination of polyethylene and wollastonite, eucalyptus fiber and maifanite powder in the sheath layer of the cable, a complex filler network is formed, which solves the problems of corrosion resistance and compression resistance of the cable in the marine environment, and significantly improves the performance and service life of the cable.
Patent Information
- Application Number
- CN202411752649.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-02
- Publication Date
- 2025-04-08
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
Existing cables are difficult to meet the needs of corrosion resistance and compression resistance in marine environments.
Polyethylene (PE) is used as the base material for the sheath layer, and wollastonite, eucalyptus fiber and maifanite powder are added to it to form a complex filler network to improve the mechanical properties and corrosion resistance of the cable.
It significantly improves the seawater corrosion resistance and impact resistance of the cable, extends the service life of the cable, and reduces the erosion of the cable by bacteria in the seawater.
Smart Images

Figure BDA0005165377730000111 
Figure BDA0005165377730000121
Abstract
Description
Technical Field
[0001] The present application relates to the technical field of cables, and more specifically, to a seawater corrosion resistant cable and a preparation method thereof. Background Art
[0002] With the in-depth development of marine resources and the development of beach tourism, the demand for offshore cables is increasing. Due to the special environment of the ocean, cables are required to have good corrosion resistance and pressure resistance. Existing cables often cannot meet the use requirements and need to be improved. Summary of the invention
[0003] In order to improve the corrosion resistance of the cable, the present application provides a seawater corrosion resistant cable and a preparation method thereof, which adopts the following technical solution:
[0004] In a first aspect, the present application provides a seawater corrosion resistant cable, comprising a cable core, an insulation layer and a sheath layer arranged in sequence, wherein the sheath layer comprises the following substances in parts by weight:
[0005] PE 100 copies;
[0006] 20-30 parts of filler;
[0007] 5-10 parts of additives;
[0008] The filler comprises eucalyptus fiber, wollastonite and medical stone powder.
[0009] By adopting the above technical solution, PE (polyethylene) is preferably used as the base material of the sheath layer. Polyethylene has good plasticity, corrosion resistance and wear resistance, which enables the cable to be stably used in seawater environment.
[0010] Wollastonite is filled in PE. The needle-like structure of wollastonite can play the role of short fibers in PE, so that PE can obtain a higher density. While increasing the impact strength of PE, it can also stably improve the mechanical strength of PE, so that the sheath layer can obtain excellent corrosion resistance and impact resistance.
[0011] The addition of medical stone powder can increase the 0-dimensional structure in PE. Medical stone powder can be loaded on the surface of eucalyptus fiber, increase the roughness of eucalyptus fiber, increase the bonding strength between eucalyptus fiber and PE, and further improve the mechanical strength of the sheath layer. Medical stone can dissociate [SiO] after contacting with water. - It can combine with bacteria to destroy the bacterial reproduction function, so that the sheath layer has a better antibacterial effect, reduce the erosion of bacteria in seawater on the sheath layer, and improve the corrosion resistance of the cable.
[0012] The addition of eucalyptus fiber can increase the linear structure in PE, and the combination of eucalyptus fiber and PE is better, which can effectively improve the density of PE. And due to the addition of wollastonite, a complex structure of long and short fibers interwoven can be formed in PE, forming a filler network in PE, which effectively improves the mechanical properties and corrosion resistance of the sheath layer.
[0013] Optionally, the wollastonite is modified wollastonite coated with calcium carbonate.
[0014] By adopting the above technical solution, since wollastonite has a relatively sharp angular structure, wollastonite is wrapped with calcium carbonate, and nano-calcium carbonate is deposited on the surface of wollastonite to wrap the sharp cable angular structure on the wollastonite, thereby retaining the strength of wollastonite and improving the interface compatibility between wollastonite and PE, so that wollastonite can effectively improve the mechanical strength of PE and enable the cable to withstand the seabed pressure for long-term use.
[0015] Optionally, the modified wollastonite is prepared as follows: calcium oxide is mixed with water to obtain a lime solution, wollastonite is immersed in the lime solution, stirred, carbon dioxide is introduced, carbonization reaction is carried out, polyethylene glycol is added to disperse, filtered, and dried to obtain a dry product, i.e., modified wollastonite.
[0016] By adopting the above technical scheme, preferably polyethylene glycol is added during the preparation process of modified wollastonite. The addition of polyethylene glycol can block the migration and adsorption of spacers, thereby inhibiting the growth of nano-calcium carbonate crystals, enabling the modified wollastonite to obtain an excellent specific surface area, which is beneficial to the combination effect of modified wollastonite and PE.
[0017] Optionally, the modified wollastonite is prepared as follows: calcium oxide is mixed with water to obtain a lime solution, wollastonite is immersed in the lime solution, stirred, carbon dioxide is introduced, carbonization reaction is carried out, polyethylene glycol is added to disperse, filtered, and dried to obtain a dry product, the dry product is mixed with water to obtain a dispersion, sodium stearate, a rare earth modifier and anhydrous ethanol are mixed to obtain an activation solution, the activation solution and the dispersion are stirred and mixed, and dried to obtain a dried product, i.e., the modified wollastonite.
[0018] By adopting the above technical solution, sodium stearate can be wrapped outside the dried product, so that the dried product can obtain better hydrophobic effect and interface compatibility, further improve the combination effect of modified wollastonite and PE, and further improve the hydrophobic effect of PE. The introduction of rare earth modifier can couple and activate the nano calcium carbonate on the surface of wollastonite, thereby improving the compatibility between wollastonite and PE macromolecular chains, effectively reducing the agglomeration phenomenon between wollastonite, and making wollastonite uniformly dispersed in PE. In addition, the rare earth elements in the rare earth modifier have a certain ultraviolet absorption effect, which can make the sheath layer obtain more suitable weather resistance and extend the service life of the cable under sunlight.
[0019] The dried product is modified by sodium stearate and a rare earth modifier. The sodium stearate and the rare earth modifier can be decomposed in anhydrous ethanol to obtain rare earth ions and stearic acid, and a small amount of rare earth stearate can be formed. The rare earth stearate can enhance the thermal stability of PE and further extend the service life of PE.
[0020] Optionally, the eucalyptus fiber is eucalyptus fiber treated with alkali solution with a concentration of 2-4%.
[0021] By adopting the above technical scheme, eucalyptus fiber is preferably treated with alkali solution. After alkali treatment, the hydroxyl groups in the eucalyptus fiber can be reduced. The hydroxyl group has good hydrophilicity. The reduction of hydroxyl content can weaken the polarity and hydrophilicity of the eucalyptus fiber, which is beneficial to enhance the bonding effect between eucalyptus fiber and PE and improve the corrosion resistance of PE.
[0022] Optionally, part of the wollastonite is loaded on the eucalyptus fiber.
[0023] By adopting the above technical solution, since part of the wollastonite is loaded on the eucalyptus fiber, that is, the wollastonite needle-shaped short fibers are loaded on the eucalyptus long fibers, a long fiber-short fiber composite structure is formed, which can make the eucalyptus fiber form a tree-like structure, which is conducive to the formation of an interlaced filler network, effectively improves the bonding strength between the filler and PE, and enables the sheath layer to obtain excellent mechanical strength.
[0024] Optionally, part of the wollastonite loaded on the eucalyptus fiber is prepared as follows: dopamine hydrochloride and n-dodecyl mercaptan are mixed to obtain a treatment solution, the eucalyptus fiber and wollastonite are immersed in the treatment solution, stirred, filtered, the solid matter is retained, washed, and dried to obtain eucalyptus fiber loaded with wollastonite.
[0025] By adopting the above technical solution, wollastonite and eucalyptus fibers are bonded by dopamine, so that a stable fiber network is formed in PE, that is, the sheath layer obtains stable mechanical strength. Dopamine can polymerize to form polydopamine, which has better ultraviolet shielding or absorption effect and hydrophobic effect, and can give the sheath layer excellent light aging resistance and corrosion resistance, thereby extending the service life of the cable.
[0026] Optionally, the eucalyptus fiber is coated with zinc oxide.
[0027] By adopting the above technical solution, zinc oxide has a better ultraviolet shielding effect. Loading zinc oxide on eucalyptus fiber can make the eucalyptus fiber obtain excellent anti-ultraviolet effect, and can fill the defects on the surface of eucalyptus fiber, effectively improving the mechanical strength and anti-light aging effect of the sheath layer.
[0028] Optionally, the eucalyptus fiber coated with zinc oxide is specifically prepared as follows: nano zinc oxide is mixed with an ethanol solution to obtain a dispersion, polyurethane is added to the dispersion and stirred to obtain a composite emulsion, the eucalyptus fiber is immersed in the composite emulsion, ultrasonically treated, filtered, and dried to obtain eucalyptus fiber coated with zinc oxide.
[0029] By adopting the above technical solution and adding polyurethane, the bonding strength between zinc oxide and eucalyptus fiber can be improved, and zinc oxide can stably improve the mechanical strength and anti-ultraviolet effect of eucalyptus fiber.
[0030] In a second aspect, the present application provides a method for preparing a seawater corrosion-resistant cable, using the following technical solution:
[0031] A method for preparing a seawater corrosion-resistant cable comprises the following steps:
[0032] S1. Sheath preparation: weigh polyvinyl chloride resin, filler and additives respectively by weight, mix, extrude and granulate to obtain sheath material;
[0033] S2. Cable preparation: Wrap the sheath around the insulating core layer to obtain the cable.
[0034] In summary, this application has the following beneficial effects:
[0035] 1. The addition of eucalyptus fiber in this application can increase the linear structure in PE, and the eucalyptus fiber has a better bonding effect with PE, which can effectively improve the density of PE. And due to the addition of wollastonite, a complex structure of long fibers and short fibers interwoven can be formed in PE, and a filler network can be formed in PE, which effectively improves the mechanical properties and corrosion resistance of the sheath layer. The addition of medical stone powder can increase the 0-dimensional structure in PE. Medical stone powder can be loaded on the surface of eucalyptus fiber, increase the roughness of eucalyptus fiber, increase the bonding strength between eucalyptus fiber and PE, and further improve the mechanical strength of the sheath layer. Medical stone can dissociate [SiO] after contacting with water. - It can combine with bacteria to destroy the bacterial reproduction function, so that the sheath layer has a better antibacterial effect, reduce the erosion of bacteria in seawater on the sheath layer, and improve the corrosion resistance of the cable.
[0036] 2. In the present application, sodium stearate can be wrapped around the dried product, so that the dried product can obtain better hydrophobic effect and interface compatibility. The introduction of rare earth modifier can couple and activate the nano-calcium carbonate on the surface of wollastonite, thereby improving the compatibility between wollastonite and PE macromolecular chains, so that wollastonite can be evenly dispersed in PE. In addition, the rare earth elements in the rare earth modifier have a certain ultraviolet absorption effect, which can enable the sheath layer to obtain more suitable weather resistance and extend the service life of the cable under sunlight. The dried product is modified by sodium stearate and rare earth modifier. Sodium stearate and rare earth modifier can form a small amount of rare earth stearate, which can enhance the thermal stability of PE and further extend the service life of PE.
[0037] 3. In this application, dopamine is used to bond wollastonite and eucalyptus fibers, so that a stable fiber network is formed in PE, that is, the sheath layer obtains stable mechanical strength. Dopamine can polymerize to form polydopamine, which has a good UV shielding or absorption effect, and can give the sheath layer excellent light aging resistance, thereby extending the service life of the cable. DETAILED DESCRIPTION
[0038] The present application is further described in detail below in conjunction with embodiments.
[0039] Preparation Example
[0040] Modified Wollastonite Preparation Example
[0041] Preparation Example 1
[0042] Mix 25g of calcium oxide with 100mL of 80℃ water to prepare lime solution. Immerse 50g of wollastonite in the mixed solution of lime solution and 200mL of water. Stir at 400rpm and introduce carbon dioxide at a flow rate of 0.8m 3 / h, carbonization reaction at 15℃, 4.37g / L polyethylene glycol is added for dispersion, and the reaction is completed when the pH value of the carbonization solution is 7±0.5. After suction filtration and drying, a dry product, i.e. modified wollastonite, is obtained.
[0043] Preparation Example 2
[0044] Mix 25g of calcium oxide with 100mL of 80℃ water to prepare lime solution. Immerse 50g of wollastonite in the mixed solution of lime solution and 200mL of water. Stir at 400rpm and introduce carbon dioxide at a flow rate of 0.8m 3 / h, 15℃ carbonization reaction, adding polyethylene glycol at 4.37g / L for dispersion, when the pH value of the carbonization solution is 7±0.5, the reaction is completed, filtered and dried to obtain a dry product. The dry product is mixed with water to obtain a dispersion with a mass concentration of 5%, sodium stearate, rare earth modifier and anhydrous ethanol are mixed to obtain an activation solution with a sodium stearate content of 2% and a rare earth modifier content of 1%, the activation solution and the dispersion are stirred and mixed at 80℃ and 700rpm for 20min, and dried to obtain a dried product, i.e., modified wollastonite.
[0045] Eucalyptus fiber preparation example
[0046] Preparation Example 3
[0047] Sodium hydroxide and water are prepared to obtain an alkali solution with a mass fraction of 2%, and the eucalyptus fiber is immersed in the alkali solution and alkali-treated for 2 hours. The fiber is taken out, washed, and dried to obtain the eucalyptus fiber after alkali treatment.
[0048] Preparation Example 4
[0049] Sodium hydroxide and water are prepared to obtain an alkali solution with a mass fraction of 3%, and the eucalyptus fiber is immersed in the alkali solution and alkali-treated for 2 hours. The fiber is taken out, washed, and dried to obtain the alkali-treated eucalyptus fiber.
[0050] Preparation example of eucalyptus fiber loaded with wollastonite
[0051] Preparation Example 5
[0052] 160 mg of dopamine hydrochloride, 100 μg of n-dodecyl mercaptan and a mixed solvent (a mixture of 20 mL of Tris-HCl and 20 mL of anhydrous ethanol) were mixed to obtain a treatment solution, and eucalyptus fiber and half of the weight of wollastonite were immersed in the treatment solution, stirred, filtered, the solid matter was retained, washed, and dried to obtain eucalyptus fiber loaded with wollastonite.
[0053] Preparation Example 6
[0054] 160 mg of dopamine hydrochloride, 100 μg of n-dodecyl mercaptan and a mixed solvent (a mixture of 20 mL of Tris-HCl and 20 mL of anhydrous ethanol) were mixed to obtain a treatment solution, and the eucalyptus fiber prepared in Preparation Example 4 and half the weight of wollastonite were immersed in the treatment solution, stirred, filtered, the solid matter was retained, washed, and dried to obtain eucalyptus fiber loaded with wollastonite.
[0055] Preparation Example 7
[0056] 160 mg of dopamine hydrochloride, 100 μg of n-dodecyl mercaptan and a mixed solvent (a mixture of 20 mL of Tris-HCl and 20 mL of anhydrous ethanol) were mixed to obtain a treatment solution, and the eucalyptus fiber prepared in Preparation Example 4, half the weight of wollastonite and medical stone powder were immersed in the treatment solution, stirred, filtered, the solid matter was retained, washed, and dried to obtain eucalyptus fiber loaded with wollastonite.
[0057] Preparation Example 8
[0058] 1 g of dry ZnO powder was weighed and added to an 80 wt% anhydrous ethanol solution, and ultrasonicated for 30 min to make it uniformly dispersed. The dispersion was transferred to an 80° C. oil bath, 0.2 g of KH550 was added and stirred for reaction for 2 h, and the white precipitate was filtered out after cooling, and dried in a vacuum oven at 75° C. for 24 h to obtain nano zinc oxide. The nano zinc oxide was mixed with 12 g of 15% ethanol solution to obtain a dispersion with a solid content of 5%. 6 g of a polyurethane emulsion with a solid content of 40% was added to the dispersion and stirred to obtain a composite emulsion. Eucalyptus fiber was immersed in the composite emulsion, ultrasonicated, filtered, and dried to obtain eucalyptus fiber coated with zinc oxide.
[0059] Example
[0060] Examples 1-3
[0061] On the one hand, the present application provides a seawater corrosion-resistant cable, comprising a cable core, an insulation layer and a sheath layer arranged sequentially from the inside to the outside, wherein the sheath layer comprises the following substances in parts by weight: PE, filler and additives, and the specific masses are shown in the table below.
[0062] The filler comprises wollastonite, eucalyptus fiber and medical stone powder in a mass ratio of 2:1:0.2.
[0063] Among them, the wollastonite is 1250 mesh wollastonite from Lingshou County Shifeng Mining Processing Plant, the eucalyptus fiber is 100 mesh eucalyptus powder with product number ZF1081, the medical stone powder is 1250 mesh medical stone powder from Lingshou County Laipeng Mineral Products Business Department, and the PE is 5000S Huajin HDPE.
[0064] The additives include antioxidant 1010 and silane coupling agent DB550 in equal weight ratio;
[0065] On the other hand, the present application provides a method for preparing a seawater corrosion resistant cable, comprising the following steps:
[0066] S1. Sheath preparation: weigh polyvinyl chloride resin, filler and additives respectively by weight, mix, extrude and granulate to obtain sheath material;
[0067] S2. Cable preparation: Wrap the sheath around the insulating core layer to obtain the cable.
[0068] Table 1 Composition of Examples 1-3
[0069] Weight / kg Example 1 Example 2 Example 3 PE 100 100 100 filler 20 25 30 Additives 5 8 10
[0070] Example 4
[0071] The difference from Example 3 is that the filler includes the modified wollastonite, eucalyptus fiber and medical stone powder prepared in Preparation Example 1 in a mass ratio of 2:1:0.2.
[0072] Example 5
[0073] The difference from Example 3 is that the filler includes the modified wollastonite, eucalyptus fiber and medical stone powder prepared in Preparation Example 2 in a mass ratio of 2:1:0.2.
[0074] Example 6
[0075] The difference from Example 3 is that the filler includes the modified wollastonite prepared in Preparation Example 2, the eucalyptus fiber prepared in Preparation Example 3 and medical stone powder in a mass ratio of 2:1:0.2.
[0076] Example 7
[0077] The difference from Example 3 is that the filler includes the modified wollastonite prepared in Preparation Example 2, the eucalyptus fiber prepared in Preparation Example 4, and medical stone powder in a mass ratio of 2:1:0.2.
[0078] Example 8
[0079] The difference from Example 3 is that the filler includes the modified wollastonite prepared in Preparation Example 2, the eucalyptus fiber prepared in Preparation Example 5, and medical stone powder in a mass ratio of 1:2:0.2.
[0080] Example 9
[0081] The difference from Example 3 is that the filler includes the modified wollastonite prepared in Preparation Example 2, the eucalyptus fiber prepared in Preparation Example 6, and medical stone powder in a mass ratio of 1:2:0.2.
[0082] Example 10
[0083] The difference from Example 3 is that the filler includes the modified wollastonite prepared in Preparation Example 2 and the eucalyptus fiber prepared in Preparation Example 7 in a mass ratio of 1:2.2.
[0084] Embodiment 11
[0085] The difference from Example 3 is that the filler includes the modified wollastonite prepared in Preparation Example 2, the eucalyptus fiber prepared in Preparation Example 4, the eucalyptus fiber coated with zinc oxide prepared in Preparation Example 8, and medical stone powder in a mass ratio of 2:0.5:0.5:0.2.
[0086] Comparative Example
[0087] Comparative Example 1
[0088] The difference between this comparative example and Example 3 is that no medical stone powder is added in this comparative example.
[0089] Comparative Example 2
[0090] The difference between this comparative example and Example 3 is that wollastonite is not added in this comparative example.
[0091] Performance testing
[0092] (1) Tensile properties: Tested using a universal tensile testing machine in accordance with GB / T1040-1992. Sample size: 150 mm × 10 mm × 4 mm double spade type, tensile speed: 50 mm / min.
[0093] (2) Izod notched impact strength: tested according to GB / T1843-1980, sample size 80 mm × 10 mm × 4 mm, notch 2 mm.
[0094] (3) Corrosion resistance test: A 3.5% NaCl solution with a salinity close to that of seawater was used as an artificial simulated seawater solution to prepare double-shovel type tensile specimens with a size of 150 mm × 10 mm × 4 mm and impact specimens with a size of 80 mm × 10 mm × 4 mm and a notch of 2 mm. The specimens were immersed in the simulated seawater solution and taken out after 56 days. Tensile and impact tests were performed in accordance with GB / T1040-1992 and GB / T1843-1980, respectively, and the strength loss of the specimens was observed.
[0095] (4) Resistance to ultraviolet light aging: Tested according to GB / T16585-1996.
[0096] Table 2 Performance test
[0097]
[0098]
[0099] After UV light aging resistance test: the tensile strength change rate of the cable prepared in Example 5 is -1.6%; the tensile strength change rate of the cable prepared in Example 8 is -1.5%; the tensile strength change rate of the cable prepared in Example 11 is -1.3%; the tensile strength change rate of the cable prepared in Comparative Example 1 is -11.8%.
[0100] Combining the performance test comparison in Table 2, we can find that:
[0101] 1. By comparing Examples 1-3 with Comparative Examples 1-2, it can be found that the impact resistance and corrosion resistance of the cables prepared in Examples 1-3 are improved, while the tensile strength is reduced. This indicates that the use of eucalyptus fiber, wollastonite and medical stone powder as fillers in the present application can form a complex filler network of long fibers, short fibers and 0-dimensional spherical particles in PE, which effectively improves the mechanical properties and corrosion resistance of the sheath layer. Medical stone powder can be loaded on the surface of eucalyptus fiber, increase the roughness of eucalyptus fiber, increase the bonding strength between eucalyptus fiber and PE, and medical stone powder can dissociate [SiO] after contacting water. - It can combine with bacteria to destroy the bacterial reproduction function, reduce the erosion of the sheath layer by bacteria in seawater, and improve the corrosion resistance of the cable. Due to the high content of wollastonite in the filler and the low tensile strength of wollastonite, the tensile strength of the cable material is reduced.
[0102] 2. By comparing Examples 4-5 with Example 3, it can be found that the impact resistance, tensile strength and corrosion resistance of the cables prepared in Examples 4-5 are all improved, which indicates that the deposition of nano-calcium carbonate on the surface of wollastonite in this application can wrap the sharp cable angular structure on wollastonite, retain the strength of wollastonite and improve the interfacial compatibility between wollastonite and PE, so that wollastonite can effectively improve the mechanical strength of PE. The dried product is modified by sodium stearate and rare earth modifier, and both sodium stearate and rare earth modifier can reduce the agglomeration of wollastonite, and sodium stearate and rare earth modifier can decompose in anhydrous ethanol to obtain rare earth ions and stearic acid, and can form a small amount of rare earth stearate, which can enhance the thermal stability of PE.
[0103] 3. By comparing Examples 6-7 with Example 3, it can be found that the impact resistance, tensile strength and corrosion resistance of the cables prepared in Examples 6-7 are improved, which means that in the present application, the eucalyptus fiber is treated with alkali solution, and the hydroxyl groups in the eucalyptus fiber can be reduced after alkali treatment. The hydroxyl group has good hydrophilicity, and the reduction of the hydroxyl content can weaken the polarity and hydrophilicity of the eucalyptus fiber, which is beneficial to enhance the bonding effect between the eucalyptus fiber and PE and improve the corrosion resistance of PE.
[0104] 4. By comparing Examples 8-10 with Example 3, it can be found that the impact resistance, tensile strength and corrosion resistance of the cables prepared in Examples 8-10 are improved. This shows that in the present application, part of the wollastonite is loaded on the eucalyptus fiber, that is, the wollastonite needle-shaped short fibers are loaded on the eucalyptus long fibers to form a long fiber-short fiber composite structure, which can make the eucalyptus fiber form a tree-like structure, which is conducive to the formation of an interlaced filler network, effectively improves the bonding strength between the filler and PE, and enables the sheath layer to obtain excellent mechanical strength.
[0105] 5. By comparing Example 11 with Example 3, it can be found that the impact resistance, tensile strength and corrosion resistance of the cable prepared in Example 11 are improved, which shows that zinc oxide in the present application has a better ultraviolet shielding effect. Loading zinc oxide on eucalyptus fiber can make the eucalyptus fiber obtain excellent anti-ultraviolet effect, and can fill the defects on the surface of eucalyptus fiber, effectively improving the mechanical strength and anti-light aging effect of the sheath layer.
[0106] This specific embodiment is merely an explanation of the present application and is not a limitation of the present application. After reading this specification, those skilled in the art may make modifications to the present embodiment without any creative contribution as needed, but such modifications are protected by the patent law as long as they are within the scope of the claims of the present application.
Claims
1. A seawater corrosion resistant cable, characterized in that: The invention comprises a cable core, an insulating layer and a sheath layer which are arranged in sequence, wherein the sheath layer comprises the following materials in parts by weight: PE 100 copies; 20-30 parts of filler; 5-10 parts of additives; The filler comprises eucalyptus fiber, wollastonite and medical stone powder.
2. The seawater corrosion resistant cable according to claim 1, characterized in that: The wollastonite is modified wollastonite coated with calcium carbonate.
3. The seawater corrosion resistant cable according to claim 2, characterized in that: The modified wollastonite is prepared as follows: calcium oxide and water are mixed to obtain a lime solution, wollastonite is immersed in the lime solution, stirred, carbon dioxide is introduced, carbonization reaction is carried out, polyethylene glycol is added for dispersion, suction filtration is performed, and drying is performed to obtain a dry product, namely the modified wollastonite.
4. The seawater corrosion resistant cable according to claim 3, characterized in that: The modified wollastonite is prepared as follows: calcium oxide is mixed with water to obtain a lime solution, wollastonite is immersed in the lime solution, stirred, carbon dioxide is introduced, carbonization reaction is carried out, polyethylene glycol is added for dispersion, suction filtration is carried out, and drying is carried out to obtain a dry product, the dry product is mixed with water to obtain a dispersion liquid, sodium stearate, a rare earth modifier and anhydrous ethanol are mixed to obtain an activation liquid, the activation liquid is stirred and mixed with the dispersion liquid, and drying is carried out to obtain a dried product, namely the modified wollastonite.
5. The seawater corrosion resistant cable according to claim 1, characterized in that: The eucalyptus fiber is eucalyptus fiber treated with alkali solution with a concentration of 2-4%.
6. The seawater corrosion resistant cable according to claim 5, characterized in that: Part of the wollastonite is supported on the eucalyptus fiber.
7. The seawater corrosion resistant cable according to claim 6, characterized in that: The preparation of part of the wollastonite loaded on the eucalyptus fiber is as follows: dopamine hydrochloride and n-dodecyl mercaptan are mixed to obtain a treatment solution, the eucalyptus fiber and wollastonite are immersed in the treatment solution, stirred, filtered, the solid matter is retained, washed, and dried to obtain eucalyptus fiber loaded with wollastonite.
8. The seawater corrosion resistant cable according to claim 5, characterized in that: The eucalyptus fiber is coated with zinc oxide.
9. The seawater corrosion resistant cable according to claim 8, characterized in that: The specific preparation of the zinc oxide coated on the eucalyptus fiber is as follows: nano zinc oxide is mixed with an ethanol solution to obtain a dispersion, polyurethane is added to the dispersion and stirred to obtain a composite emulsion, the eucalyptus fiber is immersed in the composite emulsion, ultrasonically treated, filtered, and dried to obtain the eucalyptus fiber coated with zinc oxide.
10. A method for preparing a seawater corrosion resistant cable according to any one of claims 1 to 9, characterized in that: The following steps are involved: S1. Sheath preparation: weigh polyvinyl chloride resin, filler and additives respectively by weight, mix, extrude and granulate to obtain sheath material; S2. Cable preparation: Wrap the sheath around the insulating core layer to obtain the cable.
Citation Information
Patent Citations
Nanometer-coated wollastonite powder modified waste polyethylene composite material
CN102070807A
Polyethylene foam material and preparation method thereof
CN106674687A
Composite electric power tube and preparation method thereof
CN111600273A
Flame-retardant power cable and production process thereof
CN117285772A
Composite material with EMI shielding properties and process to produce it
US20230276605A1
Cited By
Corrosion-resistant alumina fiber-containing cable outer sheath material
CN120923898A